Changing Patterns of Migration in Nepal - Baral, Madhab Prasad (Janapriya Journal of Interdisciplinary Studies, 2021)
Migration is the major factor that affects the change in the population of the given territory and its distribution of natural resources along with fertility and mortality. It also affects almost all areas of life i.e. social, economic, demographic, political, and environmental. The main cause of migration in Nepal is poverty, destitution, unequal allocation and distribution of resources, geographical variation of labor demand (Pull and push factors). The main objective of this study is to analyze the general patterns of migration in Nepal. This study is based on secondary data obtained from the census 1952/54 to 2011. The absentees and Labor statistics obtained from Nepal Labor Migration Report are also used. Regression analysis is applied to measure the trend values. Student’s t-statistic is used to measure the significance between migration to India and other countries. The percentage of absentees is threefold (2.3% to 7.3%) within the given period. The trend of absentees is steady up to 2001 and then increases rapidly. The forecasted absentees are 2.1 million for 2021 and a 2.6 million for 2031. The labor migration to India increases gradually while the migration to other countries increases rapidly. The t-test shows that there is no significant difference between trends of absentees of India and other countries. The main destination of labor migrants in Malaysia followed by Qatar and Saudi Arabia besides India. Though remittance contributes a major part of Nepal’s economy more than seventy percent of out-migrants are involved in the private job and the majority of the migrants are unskilled.